(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
The health of the human body depends on the equilibrium state of Dosha, Dhatu and Mala. Knowledge of disturbance in equilibrium of the Dosha and Dushya helps us to know the diagnosis, prognosis and treatment of the disease. The term “Vatakantaka” denotes a disease of Vata in which the pain is experienced at heel by the patient. Even though Vatakantaka has been mentioned under Vatavyadhi, the Samprapti Ghatakas and detailed pathogenesis is not available in any classical text. Such details are essential for proper planning of treatment. This study is intended to assess the Dosha and Dushya that are involved in the manifestation of Vatakantaka. 30 individuals were diagnosed as Vatakantaka were taken for the study. The Dosha and Dushya assessment were done with the help of questioner. The statistical analysis shows involvement of Vata Dosha and Asthi Dhatu in the pathogenesis of Vatakantaka.